Ocular Manifestations in Infants Resulted from Assisted Reproductive Technology (ART). - Ebrahim Jafarzadehpur; Ramin Mozafari Kermani; Ali Reza Mohhamadi; Mohammad Reza Nateghi; Abolhasan Shahzade Fazeli; Khashayar Mehdizadeh Kashi (Tehran University of Medical Sciences, 2013)
Objective: Nowadays, many infertile couples can have child by assistant reproductive technology (ART). Always the undesirable effects of these methods on newborn are considered and are evaluated. The aim of this study is to describe the impact of ART on ocular and visual performances of infants born by these methods. Materials and methods: In a cross-sectional descriptive study, 479 infants aged three-nine months presented to an optometry clinic of Child Health and Development Research Department (CHDRD), Tehran, Iran. Static retinoscopy, qualitative fixation evaluation, Hirschberg test, red reflex assessment and external eye examination were carried out. Other information such as birth weight and maturity of the infants was recorded. Results: It was possible to assess only 320 out of 479 infants due to general condition of some participants. Comparison of mean refractive error in infants' right and left eyes did not show any significant difference. Our findings confirmed that 20.3% had poor fixation, while 2.9% revealed manifest strabismus. The results also revealed the prevalences of myopia, hyperopia and emmetropia are 2.9%, 87%, and 10.1%, respectively. Red reflex abnormalities were significantly found in boys and in preterm infants (p < 0.05). Failure of fixation control was seen more frequently with increasing refractive error, which significantly developed in preterm infants (p < 0.001). Conclusion: These results reflect the necessity of more comprehensive assessments and further follow-up of infants born by ART, especially for premature male ART infants. These results also suggest the probability of fixation condition and visual deficiencies in these infants. It is recommended to pay close attention to this preliminary report about the refractive and fixation condition of the infants born after ART.